Seasonal variation in the diet of juvenile lake sturgeon, Acipenser fulvescens, Rafinesque, 1817, in the Winnipeg River, Manitoba, Canada. (1st June 2013) - Barth, C. C.; Anderson, W. G.; Peake, S. J.; Nelson, P.
Summary The lake sturgeon, Acipenser fulvescens, is a threatened species across most of its range. To understand any potential shifts in diet across season or habitat, stomach contents were examined from juvenile lake sturgeon caught in the Winnipeg River, Manitoba, Canada. This information will aid in assessment of environmental impacts and conservation initiatives for this threatened species. From 2006 to 2008 gut contents were collected from juvenile lake sturgeon using a non‐lethal gastric lavage methodology. Juvenile lake sturgeon were sampled from four discrete deep water habitat types (13.7–27.4 m depths), during the months of May, June, July and October. In total, 13 066 prey items belonging to 14 prey groups were collected from 345 juvenile lake sturgeon (251–835 mm TL). Overall, juvenile lake sturgeon consumed a low diversity of organisms; insect larvae from three invertebrate orders, Trichoptera, Diptera and Ephemeroptera, accounted for 97.4% of the total numeric abundance of prey items recovered. A relationship between size of juvenile lake sturgeon and prey quantity or type was not observed. Diet of juvenile lake sturgeon varied in relation to season, with Diptera (77.6%) being the most abundant prey in May, Trichoptera the most abundant in June (n = 3, 056, 60.4%) and July (n = 2, 055, 52.6%). During October, 96% of stomachs examined were empty. In terms of habitat type, the standardized abundance of invertebrate prey items was highest in deep water habitats characterized by medium water velocity (depths > 13.7 m) and coarse substrate (particle sizes > 0.063 mm) in May and June when compared to deep water habitats characterized by low water velocity (<0.2 m.s−1) and fine substrate (particle sizes < 0.063 mm). However, in July, the opposite was observed and prey abundance in juvenile lake sturgeon stomachs decreased with increasing particle size. Results suggest a high degree of dietary overlap among juvenile lake sturgeon from multiple size/age classes occupying deep‐water habitats of the Winnipeg River.